Income Inequality and GDP Growth Rates in CEE Countries Before and During the COVID-19 Pandemic - Mavrov, Hristo (Research Papers, 2024)
The purpose of the article is to establish the presence or absence of a relationship between GDP growth rates and income inequality. The object of the study are the most dynamic countries of Central and Eastern Europe. The time period (2000 – 2021) also allows an analysis of the role of the Covid-19 pandemic on the relationship between income inequality and economic growth. The main research question is whether a country’s accelerated development comes at the cost of increasing income inequality? Based on a descriptive analysis, it is concluded that high growth rates do not necessarily require high inequality. Rather, it is the opposite – accelerated development is also possible with decreasing income inequality.